"Most blessed of the patriarchs" : Thomas Jefferson and the empire of the imagination - Gordon-Reed, Annette; Onuf, Peter S. (Liveright Publishing Corporation, 2016)
A ground-breaking historical work that explicates Thomas Jefferson’s vision of himself, the American Revolution, Christianity, slavery and race. Thomas Jefferson is still presented today as an enigmatic figure, despite being written about more than any other Founding Father. Lauded as the most articulate voice of American freedom, even as he held people in bondage, Jefferson is variably described as a hypocrite, an atheist and a simple-minded proponent of limited government. Now, a Pulitzer Prize-winning historian and leading Jefferson scholar team up to present an absorbing and revealing character study that finally clarifies the philosophy of Jefferson. The authors explore what they call the "empire" of Jefferson’s imagination—his expansive state of mind born of the intellectual influences and life experiences that led him into public life as a modern avatar of the enlightenment, who often likened himself to an ancient figure—"the most blessed of the patriarchs".
Keywords: Jefferson, Thomas; presidentit : Yhdysvallat : 1800-luku; poliitikot; poliittiset johtajat; poliittinen historia : Yhdysvallat : 1700-luku : 1800-luku; elämäkerrat